PENGARUH PEMBERIAN KOMBINASI PUPUK ORGANIK DAN PUPUK NPK TERHADAP EFISIENSI NITROGEN PADI SAWAH INCEPTISOL - , PATRIA NOVITA KUSUMAWARDANI; , Dr. Ir. Sri Nuryani H.U., M.P., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nitrogen efficiency largely depends on the fit between plant demand and quantity of N released from applied N (mineral or organic sources ). Balance Fertilization is key to improve the efficiency of fertilizer to fulfill the crop nutrient needs. This study aims to determine the effect of cow manure, granuled organic and NPK fertilizer on N efficiency of Inceptisol paddy soil. This research conducted in May-November 2013 at the Greenhouse and Laboratory of Soil Science Department, Faculty of Agriculture, Gadjah Mada University, Yogyakarta. The Soil Analysis included the soil pH, soil EC, soil organic carbon , inorganic N, and total N, as well as the analysis of N compound and N uptake of plants. The treatments in this research are 0 tons/ha of cow manure + 0 kg/ha NPK, 0 tons/ha of cow manure + NPK fertilizer, 15 tons/ha of cow manure + without NPK, 15 ton/ha cow manure + NPK, 7,5 tons/ha of cow manure + without NPK, 7,5 tons/ha of cow manure + NPK fertilizer, 16,5 tons/ha of Petroganik + without NPK, 165 tons/ha + NPK of Petroganik, 8,25 tons/ha of Petroganik + without NPK, 8,25 tons/ha + NPK Petroganik, 12,6 tons/ha of Cakra + without NPK, 12,6 tons/ha of Cakra + NPK, 6,3 tons / ha of Cakra + without NPK and 6,3 tons/ha of Cakra + NPK . The results of the research shows that the application of the treatmens gave significantly different in terms of soil pH, organic carbon, total N, total N compound and N uptake of plants. The most optimum efficiency of nitrogen uptake is in the treatment of 15 tons/ha of cow manure without NPK at 54,56%.